The problems of the attracting of the foreign direct investments (FDI) in the top Latin American countries: Brazil, Mexico and Argentina - Olga Fomina (Ибероамериканские тетради)
Thе article discusses the role of the top Latin American countries in the international ﬂows of capital and its investment attractiveness. The emphasis is made on the role of the countries in international capital ﬂows and the relationship between Russia and Latin America in terms of investment. The analysis revealed that Latin America is becoming to play more important role nowadays on the world economic map than it used to be. Many countries are increasing their investments in Latin America despite the fact that there are a lot of diﬃculties which deal with the level and the pace of the economic growth and development in this region